IMPACT ANALYSIS OF MULTI-CELL CRASH BOX STRUCTURES WITH TRANSVERSE FUNCTIONALLY GRADED THICKNESS - Dimas Febriansyah, Bayu
Over the last decade, vehicle sales have been constantly increasing despite the fact that recent advancements in information technology drastically reduced the need to travel. As a consequence, car companies aim to design and manufacture the best vehicle possible to compete in the fierce automotive market. Weight saving is one of the most cost-efficient ways to increase the appeal of a vehicle due to the fact that it improves performance and fuel efficiency while reducing the material cost. However, weight reduction should not raise safety concerns by diminishing the vehicle’s structural crashworthiness. With increasing demands for a light weight vehicle construction, a combination of both multi-cell and functionally graded thickness concepts are introduced into a single structure. This mixed configuration is termed as functionally graded thickness multi-cell crash box and it is to be tapered transversely. Transverse direction of taper maximizes the amount of material that experiences plastic deformation at the corner sections of the crash box which will result in a higher energy absorbing capability. This research conducts FEM numerical simulation to establish the advantages of this geometrical configuration in absorbing the energy of axial impact and the influence of taper ratio on the crashworthiness performance. This is achieved by comparing conventional geometries with TFGT multi-cell crash box and analyzing 5 different taper ratios of TFGT multi-cell crash boxes. Results show that there is an improvement of up to 124 % in SEA, up to 189.5 % in MCF and up to 83.7 % in CFE. However, there is a decrease of 15.8 % in MCF compared to conventional multi-cell crash box which indicates that TFGT multi-cell crash box is less rigid but offers superior weight efficiency in terms of crashworthiness performance. Further analysis indicates that there is an increase of up to 4.158 % in crashworthiness performance when taper ratio is increased with CFE being the most affected with 0.26 sensitivity and MCF being the least affected with 0.254 sensitivity.